Pengaruh video pembelajaran interaktif terhadap hasil belajar pendidikan agama Katolik siswa SMP - Maria Hendritha Lidya Ngongo; Alexander Kiwan Bumi Lango Wuyo; Emilia Dolorosa Taek; Yoseph Lodowik Deki Dau (Pastoralia, 2025)
This study aims to analyze the effect of using interactive instructional videos on students’ learning outcomes in Catholic Religious Education at the junior secondary school level. The research employed a quantitative approach with an explanatory design and involved 88 seventh-grade students at SMPK St. Yoseph Freinademetz Kapan, East Nusa Tenggara, selected using a saturated sampling technique. Data were collected through a learning outcomes test and a questionnaire on the use of interactive instructional videos, and were analyzed using simple linear regression. The results indicate that the use of interactive instructional videos has a positive and significant effect on students’ learning outcomes (t = 35.319; p < 0.05). These findings suggest that the integration of interactive video media contributes to increased student engagement and improved understanding of Catholic Religious Education content. This study underscores the importance of utilizing digital media in religious education as a contextual and meaningful pedagogical strategy and provides practical implications for teachers in developing technology-based learning.